2017
DOI: 10.5194/aab-60-199-2017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of <i>miR-144-5p</i> and <i>miR-130b-5p</i> in dairy cattle

Abstract: Abstract. MicroRNAs (miRNAs) can coordinate the main pathways involved in innate and adaptive immune responses by regulating gene expression. To explore the resistance to mastitis in cows, miR-144-5p and miR-130b-5p were identified in bovine mammary gland tissue and 14 potential target genes belonging to the chemokine signaling pathway, the arginine and proline metabolism pathway and the mRNA surveillance pathway were predicted. Subsequently, we estimated the relative expression of miR-144-5p and miR-130b-5p i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, Lai et al [ 63 ] identified five significantly upregulated miRNAs (miR-21, miR-146a, miR-155, miR-222, and miR-383) with the potential to effectively differentiate between California mastitis test-positive milk and non-infected milk. In another study, miR-144-5p and miR-130b-5p were significantly downregulated and upregulated, respectively, in mammary gland tissues infected with mastitis compared to healthy tissues [ 84 ].…”
Section: Mirna Roles In Farm Animal Diseasesmentioning
confidence: 99%
“…Interestingly, Lai et al [ 63 ] identified five significantly upregulated miRNAs (miR-21, miR-146a, miR-155, miR-222, and miR-383) with the potential to effectively differentiate between California mastitis test-positive milk and non-infected milk. In another study, miR-144-5p and miR-130b-5p were significantly downregulated and upregulated, respectively, in mammary gland tissues infected with mastitis compared to healthy tissues [ 84 ].…”
Section: Mirna Roles In Farm Animal Diseasesmentioning
confidence: 99%
“…[31] miR-320a and miR-320b identi ed during S. uberis mastitis due to their roles in enhance immune system. In another investigation, miR-144-5p and miR-130b-5p were signi cantly down-regulated and up-regulated respectively, in mastitis animals [32]. Network analysis of differential expression genes indicated that TNF pathway had positive relationships with genes involved with immune system function [33].…”
mentioning
confidence: 94%
“…MicroRNA dysregulation has been reported to be associated with several traits in cattle, for example resistance to mastitis in dairy cattle (Li et al, 2017). Additionally, various miRNA regulome polymorphisms -within miRNA genes (miR-SNPs; single nucleotide polymorphisms), regulatory regions (miR-rSNPs), target sites (miR-TS-SNPs), and silencing machinery (miR-SM-SNPs) have also been associated with phenotypic traits and diseases Georges et al, 2007;Hrovatin and Kunej, 2018).…”
mentioning
confidence: 99%